Application of structural equation modelling to identification ofpredicting variables of a shopping centre loyalty. - Rial Boubeta, Antonio; Lamas Veiga, Ledicia; Varela Mallou, Jesús (Anales de Psicología / Annals of Psychology, 2009)
There is a vast literature about the attraction and choice of the commercial establishments, with different proposals about the involved variables and different models which try to explain both constructs. Evenso, this has not brought about definitive conclusions from the point of view of the management. But there is an agreement in affirming that there are many factors influencing the attraction and choice of a shopping centre. The classical approach point out the importance of several kinds of factors: personal characteristics of consumers (age, status, life style...), distance from the establishment to consumer, commercial and services offer and advertising. The aim of this research is to test an integral model which contains elements from the four types, from a psychosocial perspective and incorporating also consumer involvement. Thanks to the realization of a personal interview to 220 subjects and using structural equation modelling, we could check that Distance as well as the Advertising play a main role and, therefore, we must pay a special attention to both in the design and management of modern shopping centres.